The neurobiology of addiction. Issue 1 (15th January 2019) - Uhl, George R.; Koob, George F.; Cable, Jennifer
Abstract: Substance and alcohol use disorders impose large health and economic burdens on individuals, families, communities, and society. Neither prevention nor treatment efforts are effective in all individuals. Results are often modest. Advances in neuroscience and addiction research have helped to describe the neurobiological changes that occur when a person transitions from recreational substance use to a substance use disorder or addiction. Understanding both the drivers and consequences of substance use in vulnerable populations, including those whose brains are still maturing, has revealed behavioral and biological characteristics that can increase risks of addiction. These findings are particularly timely, as law‐ and policymakers are tasked to reverse the ongoing opioid epidemic, as more states legalize marijuana, as new products including electronic cigarettes and newly designed abused substances enter the legal and illegal markets, and as "deaths of despair" from alcohol and drug misuse continue. Abstract : Conceptual framework for neurobiological bases of the transition to substance use disorders.